Mobile RNAs and proteins: impacts on plant growth and productivity - Kondhare, Kirtikumar R.; Bhide, Amey J.; Banerjee, Anjan K. (Journal of Experimental Botany, 2025)
Short- and long-distance mobile signals (mobile RNAs and proteins) are integral parts of the local and systemic communications that coordinate various physiological processes at the whole-plant level and have far-reaching impacts on plant productivity. In this review, we aim to provide a comprehensive description of the integral roles of these mobile signals in controlling phenotypic traits and plant productivity. We describe how key mobile RNAs (mRNAs, small RNAs, and long non-coding RNAs) and proteins (including RNA-binding proteins) function as vital regulators of multi-faceted aspects of phenotypic traits that ultimately govern plant productivity, such as the formation of the shoot apical meristem, leaf morphology, root architecture, flowering, ripening of fleshy fruits, tuberization, crop yield, and abiotic stress responses. We also describe recent advances in the study of macromolecular transport mechanisms, such as cyclophilin-mediated transport and extracellular vesicle-based signal delivery, as well as the identification of novel signature motifs on mobile RNAs. In addition, we consider the discovery of new mobile signals and highlight how these signals can potentially be explored with advanced biotechnological interventions, virus-induced flowering, genome-editing tools, and emerging breeding approaches (e.g. the xenia-based mobile RNA delivery system for fleshy fruits) with the aim of designing strategies for enhancing valuable phenotypic traits and improving plant productivity. Mobile RNAs and proteins act as key regulators of shoot apical meristem development, leaf morphology, root architecture, flowering, fleshy fruit ripening, tuberization, yield, and responses to abiotic stresses in plants.
Keywords: Long non-coding RNA; mobile protein; mobile RNA; plant productivity; RNA-binding protein; small RNA

MYB proteins: Versatile regulators of plant development, stress responses, and secondary metabolite biosynthetic pathways - Bhatt, Preshita A.; Gurav, Tanuja P.; Kondhare, Kirtikumar R.; Giri, Ashok P. (International Journal of Biological Macromolecules, 2025)
MYB proteins are ubiquitous in nature, regulating key aspects of plant growth and development. Although MYB proteins are known for regulating genes involved in secondary metabolite biosynthesis, particularly phenylpropanoids, their roles in terpenoid, glucosinolate, and alkaloid biosynthesis remain less understood. This review explores the structural and functional differences between activator and repressor MYB proteins along with their roles in plant growth, development, stress responses, and secondary metabolite production. MYB proteins serve as central hubs in protein-protein interaction networks that regulate expression of numerous genes involved in the adaptation of plants to varying environmental conditions. Thus, we also highlight key interacting partners of MYB proteins and their roles in these adaptation mechanisms. We further discuss the mechanisms regulating MYB proteins, including autoregulation, epigenetics, and post-transcriptional and post-translational modifications. Overall, we propose MYB proteins as versatile regulators for improving plant traits, stress responses, and secondary metabolite production.
Keywords: Activator; defense; Development; MYB protein; Repressor; Secondary metabolites